What Factors Affect Tax Avoidance? - Carrie, Monica Yuly; Susanty , Meinie (Universitas Kristen Maranatha, 2024)
Purpose: This study is to obtain empirical evidence about the effect of audit committees, institutional ownership, independent commissioners, company size, sales growth, leverage, profitability, capital intensity, and CSR disclosure on tax avoidance. Design/methodology/approach: This study uses a sample of all manufacturing companies listed on the Indonesia Stock Exchange, also known as the IDX, from 2019 to 2021, with 62 listed manufacturing companies used as samples in this study. This sample selection uses the purposive sampling method with 186 research data and uses multiple linear regression for hypothesis testing. Findings: The findings of this study indicate that audit committee, company size, leverage, and profitability affect tax avoidance, while the other 5 variables, namely institutional ownership, independent commissioners, sales growth, capital intensity, and CSR disclosure, have no effect on tax avoidance. Research Limitations/Implications : The implications of this study are provide input to companies in making corporate tax planning in the legal corridor-tax avoidance which is influenced by corporate governance factors, characteristics and corporate social responsibility. The implications also provide input to Indonesia's tax regulators in conducting an analysis of the compliance of public company taxpayers and input in making tax regulations. Keywords: Audit Committee, Institutional Ownership, Independent Commissioner, Capital Intensity, and CSR Disclosure.